Basketball affects bone mineral density accrual in boys more than swimming and other Kampfsportarten: 9-mo follow-up - Agostinete, R. R.; Lynch, K. R.; Gobbo, L. A.; Spiguel Lima, M. C.; Ito, I. H.; Luiz-de-Marco, R.; Rodrigues-Junior, M. A.; Fernandes, R. A. (Journal of Clinical Densitometry, 2016)
The objective of this study was to analyze the effect of different sports on bone mineral density (BMD) accrual among male adolescents during a 9-mo follow-up. The sample was composed of 82 boys (control [n=13], basketball [n=14], karate [n=9], soccer [n=18], judo [n=12], and swimming [n=16]) who were followed up for 9?mo (from October 2013 to August 2014). BMD (gram per square centimeter) was assessed at baseline and follow-up using a dual-energy X-ray absorptiometry scanner, whereas somatic maturation was estimated through the use of the peak height velocity. Vitamin D consumption was assessed by questionnaire. After 9 mo of follow-up, all groups (including the control group) presented significant BMD accrual (overall sample: 4.5% in the whole body). On the other hand, the basketball group presented higher BMD accrual in the upper limbs (17.6%) than the control group (7.2%). A similar difference was observed in whole-body BMD (control group: 4.1% vs basketball group: 7.1%). The basketball group had significantly higher BMD gains than the control group and other sports groups.